Posterior concentration of Wolbachia during the early embryogenesis of the host dynamically shapes the tissue tropism of Wolbachia in host Trichogramma wasps - Zhou, Jin-Cheng; Dong, Qian-Jin; Shang, Dan; Ning, Su-Fang; Zhang, Huan-Huan; Wang, Ying; Che, Wu-Nan; Dong, Hui; Zhang, Li-Sheng (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The bacterial endosymbiont, Wolbachia spp. induce thelytokous parthenogenesis in certain parasitoid wasps, such as the egg parasitoid wasps Trichogramma spp. To complete the cycle of vertical transmission, Wolbachia displays efficient transovarial transmission by targeting the reproductive tissues and often exhibits strong tissue-specific tropism in their host. Method The present study aimed to describe the basic Wolbachia distribution patterns that occur during the development of Wolbachia-infected, thelytokous Trichogramma dendrolimi, and T. pretiosum. We used fluorescence in situ hybridization (FISH) to investigate Wolbachia signal dynamics during early embryogenesis (from 30 to 120 min). Wolbachia titers and distributions from the embryo to adult stages of Trichogramma after early embryogenesis were detected by absolute quantitative polymerase chain reaction (AQ-PCR) and FISH. The symmetry ratios (SR) of the Wolbachia signals were calculated using the SR odds ratios in the anterior and posterior parts of the host. The SR was determined to describe Wolbachia tropism during early embryogenesis and various developmental stages of Trichogramma. Results Wolbachia was concentrated in the posterior part of the embryo during early embryogenesis and the various developmental stages of both T. dendrolimi and T. pretiosum. Wolbachia density increased with the number of nuclei and the initial mitotic division frequency during early embryogenesis. The total Wolbachia titer increased with postembryogenesis development in both T. dendrolimi and T. pretiosum. However, the Wolbachia densities relative to body size were significantly lower at the adult and pupal stages than they were at the embryonic stage. Discussion The present work revealed that posterior Wolbachia concentration during early host embryogenesis determined Wolbachia localization in adult wasps. By this mechanism, Wolbachia exhibits efficient vertical transmission across generations by depositing only female Wolbachia-infected offspring. The results of this study describe the dynamics of Wolbachia during the development of their Trichogramma host. The findings of this investigation helped clarify Wolbachia tropism in Trichogramma wasps.